Incidence of Stroke Cases at Blambangan General Hospital of Banyuwangi in January-December 2022: A Descriptive Study - Hastuti, Riani Dwi; Setyawan, Andar; Handayani, Indah Ari; Khalisha, Putri Nabila (Universitas Airlangga, 2024)
Highlight: The majority of stroke cases at Blambangan General Hospital in Banyuwangi are ischemic strokes. The age group that experienced the most strokes was >40 years. The gender that experienced the most strokes was female. ABSTRACT Introduction: Stroke is a leading cause of morbidity in Indonesia. It significantly contributes to the overall burden of disease and places a substantial impact on the health of the population in Indonesia. Objective: The purpose of this study was to show the incidence of stroke cases in the Blambangan General Hospital in Banyuwangi. Understanding the prevalence of strokes at this particular hospital is critical for identifying patterns, improving patient care, and taking preventive actions to deal with this important health issue. Methods: This study used a retrospective cross-sectional sampling method to look at all 342 inpatient stroke cases that were treated in the neurology department of Blambangan General Hospital in Banyuwangi in 2022. All of their data was collected and analyzed. Results: Most cases of stroke in this study were ischemic strokes, with a total of 212 cases (62.0% of all cases). The age group that experienced the most strokes was over 40 years old (96.2%) and female (56.4%). More than half of stroke patients had hypertension, and 80.1% had diabetes mellitus. Conclusion: This study found that ischemic stroke survivors, mostly female and aged over 40, were frequently associated with diabetes mellitus and hypertension. These findings provide insights into the frequency of these stroke types within the examined population.